Research on promotional campaign of F&N fruit juice - Ardiles, ak. Gabrial (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Fruit juice is one of the most favourable products because of its refreshing and healthy content. However F & N’s “Fruit Tree” is less known compared to other brands such as ‘Yeo’s,”Drinho” and “Cheers”. It was due to lack of aggressive campaign and promotion to the end user. This research is conducted to analyze, to identify and to create the effective campaign for this fruit juice product.